The red shoes - Fowler, Gloria; Andersen, H. C., (Hans Christian), 1805-1875.; Yoo, Sun-Young ([S.l.] : AMMO, 2008)
Karen, orphaned when her beloved mother, a shoemaker, dies, is left with only a pair of red leather shoes which soon become attached to her feet, and when a spoiled princess demands the shoes, Karen must somehow find a way to save herself and her mother's memory.
"Based on the original story The red shoes by Hans Christian Andersen"--Colophon.
Publisher's Weekly.
K-3
Keywords: Fairy tales; Pride and vanity -- Juvenile fiction; Shoes -- Juvenile fiction; Fairy tales; Pride and vanity -- Fiction; Shoes -- Fiction; Fairy tales; Pride and vanity -- Fiction; Shoes -- Fiction